Analisis Dispersi SO₂ dan NO₂ di Kawasan Budaya Kota Yogyakarta Menggunakan Model AERMOD: Indonesia - Hasanah, Ana Uswatun; Lutfia, Kendra Isma; Wantoputri, Noviani Ima; Kusumawati, Regina Dewi (Asian Journal of Innovation and Entrepreneurship, 2025)
Yogyakarta City, as a cultural and tourism hub, experiences a high level of transportation activity, particularly in its historical and strategic areas. This results in an increase in emissions, such as sulfur dioxide (SO₂) and nitrogen dioxide (NO₂), which have a negative impact on public health and the environment. This study aims to analyze the spatial dispersion of SO₂ and NO₂ pollutants from transportation sector activities using the AERMOD model. The results of the emission inventory on 10 research roads indicate that the highest SO₂ emission load is found on Jalan KH Ahmad Dahlan, at 8,315.31 g/hour. In contrast, the highest NO₂ emission load is observed on Jalan Brigjen Katamso, at 704.50 g/hour. The type of diesel-fueled motorized vehicles, although relatively fewer in number, has a much greater contribution to SO₂ and NO₂ emissions than gasoline-fueled vehicles, especially motorcycles. The modeling results using AERMOD showed that the maximum concentrations of SO₂ and NO₂ reached 53.1 μg/m³ and 118 μg/m³, respectively, with the distribution pattern influenced by the dominant wind direction from the northwest and relatively low wind speed (0.5–2.1 m/s). The spatial pattern of the simulation results showed a decrease in concentration as the distance from the emission source to the sensitive receptors increased, such as the Malioboro and   Alun-Alun Kidul tourist areas. Validation of the model against actual monitoring data (Impinger instrument measurement results) yielded an average RMSPE value of 24% for the SO₂ parameter, which remained within the model validation tolerance limit. However, the RMSPE value for the NO₂ parameter reached 59%, indicating that the model's concentration estimate tended to overestimate the actual value.